Active Learning as a Solution to Student Burnout in Islamic Religious Education: Views from Madrasah - Khomsiah, Khomsiah; Hidayah, Fathi; Aniati, Ana; Hasan Baharun (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
This research focuses on applying active learning methods to overcome student burnout in Islamic religious education in madrasahs. The main objective of this research is to evaluate the effectiveness of project-based Learning, role-playing and simulation, problem-based Learning, and collaborative activities in increasing student motivation, engagement, and skill development. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with students, teachers, and school principals at Madrasah Ibtida'iyah Negeri 3 Banyuwangi and direct observations in the classroom. The research results show that active learning methods significantly reduce student burnout and increase their motivation and involvement in the learning process. Project-based learning helps students relate theory to actual practice, while role-playing and simulations enrich their learning experience. Problem-based learning encourages students to think critically and analytically, while collaborative activities strengthen students' cooperation and social skills. These findings confirm that active learning methods can effectively improve the quality of Islamic religious education in madrasahs. The implication of this research is the need to integrate active learning methods in the madrasa curriculum to create a more dynamic learning environment and support student welfare. This research also underscores the importance of developing more inclusive and evidence-based education policies to comprehensively accommodate students' needs and potential.